2015
DOI: 10.3109/09546634.2015.1054776
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and cost of etanercept in long-term psoriasis: Rational use in clinical practice

Abstract: We present our experience in regular clinical practice with etanercept, showing it to be an effective, safe, and versatile drug that permits patient-tailored treatment, delivering a frankly satisfactory control of our psoriasis patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 22 publications
2
8
0
Order By: Relevance
“…Of the partial economic evaluations for moderate–severe PSO, four ( n = 505 patients treated with ETN) were based on observational studies in a real-life clinical context [2730], and one study used modeling techniques [31]. All of the studies adopted the perspective of the NHS (only pharmacological costs), with the exception of one cost-minimization study which also considered indirect costs owing to loss of productivity [28].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the partial economic evaluations for moderate–severe PSO, four ( n = 505 patients treated with ETN) were based on observational studies in a real-life clinical context [2730], and one study used modeling techniques [31]. All of the studies adopted the perspective of the NHS (only pharmacological costs), with the exception of one cost-minimization study which also considered indirect costs owing to loss of productivity [28].…”
Section: Resultsmentioning
confidence: 99%
“…The annual cost per patient with moderate–severe PSO who was treated with ETN ranged from €4986 (maintenance phase cost in patients receiving intermittent treatment) to €12,327/patient-year (maintenance phase cost in patients receiving continuos treatment) [30]. For patients who experienced loss of response to the ETN treatment, the annual escalation cost owing to dose duplication ranged from €14,580 (12-week intensification) to €18,908 (31-week intensification)/patient-year [31] (Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the chronic condition psoriasis, for example, Health Technology Appraisals by the UK economics watch dog NICE commonly assume greater health benefit for biologic drugs, impacting on a “value for money” type of approach for these high‐cost drugs. By contrast, we here exploit detailed knowledge of the response of psoriasis to phototherapy as well as comparator treatments in order to simplify modelling by aligning it with clinical practice: regardless of a specific PASI improvement, a given patient is likely to progress along the treatment pathway if a subjectively “insufficient” experienced level of disease control is encountered, as shown previously in detail for methotrexate . We therefore also disregard potential savings by reduced requirement for steroid cream treatment, which we have previously shown for NB‐UVB, as this specific is likely be comparable for any effective intervention.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is worth noting that we have previously shown that the degree of disease control by NB-UVB is comparable to that achieved by methotrexate under realworld conditions, 6,17,18 and that response rates are similar to clinical study results reported for apremilast, DMF and etanercept. [19][20][21] Although the subjectively experienced degree of disease control, that is the "health benefit," is likely higher using a biologic drug, it is therefore reasonable to assume that any given patient will not continue phototherapy in the absence of a subjective benefit justifying treatment attendance.…”
Section: Actual-versus Qaly-based Costsmentioning
confidence: 99%